Fully Integrated Time-Gated 3D Fluorescence Imager for Deep Neural Imaging - Choi, Jaebin; Taal, Adriaan J.; Meng, William L.; Pollmann, Eric H.; Stanton, John W.; Lee, Changhyuk; Moazeni, Sajjad; Moreaux, Laurent C.; Roukes, Michael L.; Shepard, Kenneth L. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
This paper presents a device for time-gated fluorescence imaging in the deep brain, consisting of two on-chip laser diodes and 512 single-photon avalanche diodes (SPADs). The edge-emitting laser diodes deliver fluorescence excitation above the SPAD array, parallel to the imager. In the time domain, laser diode illumination is pulsed and the SPAD is time-gated, allowing a fluorescence excitation rejection up to O.D. 3 at 1 ns of time-gate delay. Each SPAD pixel is masked with Talbot gratings to enable the mapping of 2D array photon counts into a 3D image. The 3D image achieves a resolution of 40, 35, and 73 mu m in the x, y, and z directions, respectively, in a noiseless environment, with a maximum frame rate of 50 kilo-frames-per-second. We present measurement results of the spatial and temporal profiles of the dual-pulsed laser diode illumination and of the photon detection characteristics of the SPAD array. Finally, we show the imager's ability to resolve a glass micropipette filled with red fluorescent microspheres. The system's 420 mu m-wide cross section allows it to be inserted at arbitrary depths of the brain while achieving a field of view four times larger than fiber endoscopes of equal diameter.
Keywords: AVALANCHE-DIODE ARRAY; SENSORS; FILTER; BRAIN